Judicious DICER1 testing and surveillance imaging facilitates early diagnosis and cure of pleuropulmonary blastoma. Issue 9 (13th May 2014) - Schultz, Kris Ann P.; Harris, Anne; Williams, Gretchen M.; Baldinger, Shari; Doros, Leslie; Valusek, Patricia; Frazier, A. Lindsay; Dehner, Louis P.; Messinger, Yoav; Hill, D. Ashley
<x xml:space="preserve">Abstract</x> Pleuropulmonary blastoma (PPB) and Sertoli–Leydig cell tumor (SLCT) are both associated with germline mutations in DICER1. In this brief report, a maternal history of SLCT led to identification of a deleterious DICER1 mutation in the patient and her asymptomatic infant. Radiographic screening revealed a large Type I PPB, which was completely resected. Identification of DICER1 mutation carriers and imaging of children at risk for PPB may allow detection of PPB in its earliest and most curable form, leading to increased likelihood of surgical cure and decreased risks of treatment‐related late effects. Pediatr Blood Cancer 2014;61:1695–1697. © 2014 Wiley Periodicals, Inc.